The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.5937/ijcrsee2001015n
|View full text |Cite
|
Sign up to set email alerts
|

Trust as a Cognitive Base of Social Cohesion in the University Communities

Abstract: The present article continues the cycle of the cognitive researches of the phenomenon of social cohesion in education, in particular, in the university communities. It contains the cognitive research of trust and its foundation as the central focus of social cohesion. The purpose of the study is to identify the level of trust which is connected with the social cohesion in university communities, to test the author’s questionnaire and to determinate the further steps for the trust enhancement in the educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…This research has been held among the employees of the above universities (mostly lecturers) and students. The aim of the research is to identify the level of trust in the above communities and to mark the weak points in the domains of trust for further strengthening of it by appropriate trainings and other social and educational tools (Nesterova et al, 2020). According to this research we can confirm the statement that one of the key factors of the social cultural space development is based on the appropriate values, trust, in particular.…”
Section: Social Cohesion As a Value-based Complex Social Phenomenon Amentioning
confidence: 57%
See 2 more Smart Citations
“…This research has been held among the employees of the above universities (mostly lecturers) and students. The aim of the research is to identify the level of trust in the above communities and to mark the weak points in the domains of trust for further strengthening of it by appropriate trainings and other social and educational tools (Nesterova et al, 2020). According to this research we can confirm the statement that one of the key factors of the social cultural space development is based on the appropriate values, trust, in particular.…”
Section: Social Cohesion As a Value-based Complex Social Phenomenon Amentioning
confidence: 57%
“…There were some researches of the level of social cohesion and the level of trust in the university communities. One of them was the research of the level of social cohesion in the university community of NPDU (Nesterova et al, 2019) and another research regarding on the level of trust in the university communities of National Pedagogical Dragomanov University (NPDU) and National University of Life and Environmental Sciences (NULES) (Nesterova et al, 2020). This research has been held among the employees of the above universities (mostly lecturers) and students.…”
Section: Social Cohesion As a Value-based Complex Social Phenomenon Amentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous research, the authors had already analysed social cohesion (Nesterova et al 2019(Nesterova et al , 2020Dielini et al 2022). The results of the study showed an average level of social cohesion among both students and staff, with slight variations depending on the field of activity.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The new social situation of the pandemic has confirmed that the current challenge for all countries (not only for the European Union or Ukraine) is to revise the real (not declared) set of values. According to this revised set of values, priorities in social and educational policy should be formulated (Nesterova et al, 2020. Values determine the level of social cohesion in society and its features as a social phenomenon.…”
Section: Introductionmentioning
confidence: 99%